(untitled) (Global Journal of Management and Business Research, 2012)
A record of all transactions made between one particular country and all other countries during a specified period of time is known as Balance of Payment (BOP). There are many factors that determine the position of balance of payments in the country either it is surplus or deficit. This study analyzes the statistical data of BOP of Pakistan from 1986 to 2010 and is an attempt to find out possible reasons for adverse BOP of Pakistan since its creation. The analysis shows that out of eight variables only two variables proved to be statistically significant namely foreign direct investment inflows and worker#x2019;s remittances. However the impact of these variables on BOP turned out to be negative.